2015
DOI: 10.1002/lary.25539
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery of the orbital apex: Outcomes and emerging techniques

Abstract: The endoscopic approach to the orbit apex offers significant advantages over traditional external approaches, and should be the preferred approach for all medial and inferior lesions. A two-surgeon multihanded technique can help facilitate difficult cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…6,9 Binarial transseptal approaches have been described to augment endoscopic dissection and retraction using a 4-handed technique. 5,[10][11][12] In 3 of our reported cavernous hemangioma resections, we utilized a cryoprobe device to securely grasp the lesion and facilitate the dissection. We have found that the texture of vasculogenic lesions can be difficult to grasp and dissect from surrounding fat using standard sinus instruments, even with assistance from ophthalmology delivering the lesion medially.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Binarial transseptal approaches have been described to augment endoscopic dissection and retraction using a 4-handed technique. 5,[10][11][12] In 3 of our reported cavernous hemangioma resections, we utilized a cryoprobe device to securely grasp the lesion and facilitate the dissection. We have found that the texture of vasculogenic lesions can be difficult to grasp and dissect from surrounding fat using standard sinus instruments, even with assistance from ophthalmology delivering the lesion medially.…”
Section: Discussionmentioning
confidence: 99%
“…Modern neurosurgery targets the best possible minimal invasive surgical outcome with minimal tissue damage and maximal patients' cosmetic satisfaction, pain, and functional outcomes (Koerbel et al, ; Abdel Aziz et al, ; Reisch et al, ; Tatarli et al, ; Ulutas et al, ). The recently introduced endoscopic approaches to the orbit apex offers significant advantages and better surgical outcomes over external approaches, and was suggested to be the preferred approach for all medial and inferior lesions (Stokken et al, ). The ocular motor nerves are under risk of injury during orbital approaches to any kind of surgery directed to this region thus; a precise knowledge of their relationships with the muscles and the surrounding structures through microdissection and determination of landmarks may help surgeons avoiding nerve injuries during transcranial and endoscopic orbital approaches.…”
Section: Discussionmentioning
confidence: 99%
“…2). The most commonly used endonasal endoscopic approaches for lesions that affect vision or cause diplopia are the following: 1) the trans-sellar route for sellar lesions, most commonly for pituitary adenomas and Rathke cleft cysts, 2) trans-sellar, trans-tubercular and trans-planum route for lesions that extend into the suprasellar, prechiasmatic and retrochiasmatic cisterns, most commonly for large or giant pituitary adenomas, tuberculum meningiomas, and craniopharyngiomas, 3) trans-sellar and extended approach to cavernous sinus and Meckel cave most commonly used for invasive pituitary adenomas, invasive parasellar meningiomas, schwannomas, and clival chordomas, 4) trans-clival approach most commonly used for invasive parasellar meningiomas and clival chordomas, and 5) endonasal approach to medial optic canal, orbital apex and orbit, most commonly used for meningiomas, hemangiomas, fibrous dysplasia, malignancies, and inflammatory processes (32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Common Parasellar Endoscopic Approachesmentioning
confidence: 99%